Work Environment Improvement to Reduce Dust and Microorganism Exposures in Community Rice Mill at Buyor Village, Chokchai District, Nakhon Ratchasima Province - Boonruksa, Pongsit; Limmongkon, Yuparat (Journal of Health Science of Thailand, 2018)
The objective of this study was to reduce dust and microorganism in a community rice mill using local exhaust ventilation as a work environment improvement. Total dust, respirable dust, bacteria, and fungi were measured before and after the improvement at the areas of loading and feeding, grading and polishing, bran and broken rice outlet, and packing. The methods of data collection and analysis were NIOSH #0500 for total dust, and #0600 for respirable dust, whereas NIOSH #0800 was used for bacteria and fungi. The results showed that the highest concentration of total dust, respirable dust, bacteria, and fungi were found at the loading and feeding area before the improvement. When installing local exhaust ventilation at that area, it was able to reduce the total dust and respirable dust in the community rice mill up to 90.26% and 52.17%, respectively. In addition to dust concentration, it also reduced the concentration of microorganism up to 54.38% for bacteria and 94.75% for fungi. Moreover, the results revealed that a positive correlation was obtained in the concentration of total dust with respirable dust (r2 =0.84), but it was not correlated with bacteria and fungi. In addition to the installation of local exhaust ventilation at the loading and feeding area, good maintenances, and 5S activities should be implemented to reduce the accumulation of dust and microorganism in community rice mills.